The school principals' leadership styles in low-performing secondary school in Bintulu district / Caroline Cathy Nubun - Nubun, Caroline Cathy (2013)
The study was conducted to explore the principals' leadership styles in lowperforming secondary schools in Bintulu district, Sarawak. 100 respondents who were the teachers in the secondary schools involved in this study as the sample. The questionnaire used was adopted from the instrument Leadership Behavioral Description Questionnaire (LBDQ XII) by Hemphill and Coon (1957) then revised by House (1974). The quantitative data was being analyzed by using SPSS version 16. From this study, it was found that the principal practiced more on the style of initiating structure compared to consideration. The findings revealed that there was significance difference between male and female teachers on the principals' leaderships styles. In addition, the study shown that there was a significant difference between novice teachers and experienced teachers. However, there was no significance difference between one and two sessions of schooling. Lastly, the study revealed that the principals' leadership styles in low-performing secondary schools in their management.